2004
DOI: 10.1002/ffj.1370
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the essential oils from Turkish and Honduras Styrax

Abstract: The essential oil composition of two different styrax gums, Asian and American were analysed by GC and GC-MS. Fifty-eight components representing more than 99.4% of the oil from Asian styrax gum and 57 components representing more than 99% of the oil from American styrax gum were identified. The major components were styrene (70.4 and 30.9% respectively), α-pinene (19.4 and 19.6%) and β β β β β-caryophyllene (0.2 and 20.2%) for the two oils. These results show that we could identify an Asian from an American s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 4 publications
2
41
0
7
Order By: Relevance
“…The major components of the leaf oil were reported to be styrene, dlimonene, α-pinene and β-pinene, and that of the stem oil were germacrine D, α-cadinol, d-limonene, α-pinene, and β-pinene [45], [46]. These essential oils showed anti-inflammatory activity with low cytotoxicity thus backing its traditional use in treating inflammation.…”
Section: Discussionmentioning
confidence: 97%
“…The major components of the leaf oil were reported to be styrene, dlimonene, α-pinene and β-pinene, and that of the stem oil were germacrine D, α-cadinol, d-limonene, α-pinene, and β-pinene [45], [46]. These essential oils showed anti-inflammatory activity with low cytotoxicity thus backing its traditional use in treating inflammation.…”
Section: Discussionmentioning
confidence: 97%
“…Styrene is the major component in both oils, but it is more abundant in the Asian Storaque (70.4%) than in the American one (30.9%). On the other hand, β-caryophyllene is more abundant in the American Storaque (20.2%) together with α-pinene (19.6%), than in the Asian Storaque (0.2%) (Fernandez et al, 2005). Some of the substances identified by Fernandez et al (2005) were also observed by Boelens et al (1982) in the same balsam, such as the styrene, p-cymene, limonene, terpinolene, cinnamyl alcohol, α-cubebene, and other substances in minor quantities.…”
Section: Liquid Storaquementioning
confidence: 96%
“…L. orientalis is a herbaceous plant known to have medicinal and cosmetic properties and is widely used in phytotherapy in the Mediterranean region. The storax produced by injuring L. orientalis has good antiseptic properties (Fernandez, 2005; Lee et al, 2009). Also it is used as a topical parasiticide, expectorant and for the treatment of some skin diseases in Turkish folk medicine.…”
Section: Introductionmentioning
confidence: 99%